Disciplined Sciences? Differentiation of Academic Subjects at Eighteenth and Nineteenth Century German Universities - Füssel, Marian (Historical Studies on Central Europe, 2022)
The historiography of individual academic subjects and disciplines is an indispensable part of both university history and the history of science. Scientific disciplines are a relatively recent phenomenon from the university-historical perspective of longue durée, whose study has nevertheless undergone some striking developments in the past forty years. At the level of the historiography of disciplines, structural patterns of academic subject histories are highlighted, leading from the philosophy of science of the 1970s to the cultural turns of the 1990s and 2000s. Disciplines are partial results of a broader process of diversification, fragmentation, and specialisation that began as early as the eighteenth century. This survey reconstructs processes of disciplinary differentiation and disciplining from the order of faculties to the “regime of disciplines” in the transition from the eighteenth to the nineteenth century, focusing on the University of Göttingen as a dynamic hub of development. Using the example of German universities, the genealogies of individual chairs, subjects, and disciplines are traced. Special attention is paid to the dual character of disciplining as a submission to a system of rules and the organisation of knowledge.